Origin of the Fermi arcs in cuprates: a dual role of quasiparticle and pair excitations. (2nd November 2018) - Sacks, William; Mauger, Alain; Noat, Yves
Abstract: Angle resolved photoemission spectroscopy (ARPES) mesurements in cuprates have given key information on the temperature and angle dependence of the gap ( d -wave order parameter, Fermi arcs and pseudogap). We show that these features can be understood in terms of a Bose condensation of interacting pairons (preformed hole pairs which form in their local antiferromagnetic environment). Starting from the basic properties of the pairon wavefunction, we derive the corresponding k -space spectral function. The latter explains the variation of the ARPES spectra as a function of temperature and angle up to T *, the onset temperature of pairon formation. While Bose excitations dominate at the antinode, the fermion excitations dominate around the nodal direction, giving rise to the Fermi arcs at finite temperature. This dual role is the key feature distinguishing cuprate from conventional superconductivity.